CHEMICAL CHARACTERISTICS AND ORIGIN OF DISSOLVED ORGANIC MATTER IN THE YUKON RIVER - Guéguen C.; Guo L.; Wang D.; Tanaka N.; Hung C.-C. (My University, 2006)
Monthly (or bi-weekly) water samples were collected from the Yukon River, one of the largest rivers in North America, at a station near the US Geological Survey Stevens Village hydrological station, Alaska from May to September 2002, to examine the quantity and quality of dissolved organic matter (DOM) and its seasonal variations. DOM was further size fractionated into high molecular weight (HMW or colloidal, 1 kDa-0.45 μm) and low molecular weight (LMW, <1 kda) fractions. dissolved organic carbon (doc), colored matter (c-dom) and total carbohydrate (tcho) species were measured in the size fractionated dom samples. concentrations of doc as high 2830 μmol-c l-1 during the spring breakup in May and decreased significantly to 508-558 μmol-C l-1 during open-water season (June-September). Within the DOC pool, up to 85% was in the colloidal fraction (1 kDa-0.45 μm) in early May. As DOC concentration decreased, this colloidal portion remained high (70-85% of the bulk DOC) throughout the sampling season. Concentrations of TCHO, including monosaccharides (MCHO) and polysaccharides (PCHO), varied from 722 μmol-C l-1 in May to 129 μmol-C l -1 in September, which comprised a fairly constant portion of bulk DOC (24±2%). Within the TCHO pool, the MCHO/TCHO ratio consistently increased from May to September. The C-DOM/DOM ratio and the size fractionated DOM increased from May to September, indicating that DOM draining into the Yukon River contained increased amounts of humified materials, likely related to a greater soil leaching efficiency in summer. The average composition of DOM was 76% pedogenic humic matter and 24% aquagenic CHO. Characteristics of soil-derived humic substances and low chlorophyll-a concentrations support a dominance of terrestrial DOM in Yukon River waters.
Keywords: CARBOHYDRATE; COLORED DISSOLVED ORGANIC MATTER; DISSOLVED ORGANIC CARBON; SOIL ORGANIC CARBON; YUKON RIVER